REVIEW OF THE POSITION OF E-SPORT AS A SPORT IN INDONESIA - Rezha Arzhan Hidayat; Muhamad Ichsan Sabillah (Faculty of Sport Science, Universitas Negeri Yogyakarta, 2021)
E- sport at this time is again growing very rapidly. Just like any other sporting branch, esports is also organized sports with special training. This research aims to recognize the role of E- Sport as one of the branches of exercise by analyzing articles and books that have existed, this research uses a qualitative descriptive research approach. The results of this research prove that e-sport is a branch of sports because it has factors such as the value of justice, the value of certainty, the value of expediency. The recognition of e-sport as a branch of sports leads to many problems in residents whether e-sport is categorized as a type of exercise. Sourced from inference, e-sport can be categorized as sporting achievements, therefore e-sport is chosen as a sport that has 4 lower factors, namely, competitive factors, sportsmanship factors, achievement factors, and motor factors.